Solar power sail membrane prototype for OKEANOS mission. Issue 9 (1st May 2021) - Matsushita, Masanori; Chujo, Toshihiro; Matsumoto, Jun; Mori, Osamu; Yokota, Rikio; Toyota, Hiroyuki; Satou, Yasutaka; Okuizumi, Nobukatsu; Kato, Hideki; Nakamura, Tetsuya; Shibata, Yuichi; Nakao, Tatsuro; et al.
Abstract: This paper reports on the manufacturing and evaluation of a solar power sail membrane prototype for the OKEANOS project. The in-house prototype was built by the Institute of Space and Astronautical Science, Japan Aerospace Exploration Agency. Mechanical and electrical evaluation tests were conducted. The membrane, thin-film solar cells, reflectivity control devices were good condition after the manufacturing and handling. The improvements in the manufacturing process and design were found. The manufacturing process and design were fundamentally established. After the prototype, improvement plans for the manufacturing process and design were tried. We have a prospect of manufacturing the flight model sail and continue to the development.